THU0449 Evidence based development of criteria for complete response in patients with chronic refractory gout. (15th June 2017) - Schlesinger, N; Khanna, P; Yeo, A; Lipsky, P
Abstract : Background: Preliminary criteria for remission in gout patients have recently been proposed. These include serum urate, acute flares, tophus, pain and patient global assessment. 1 These preliminary criteria were based on consensus exercises and have not yet been tested in a large clinical trial database of chronic gout patients. Because of the availability of clinical results from subjects with chronic refractory gout treated with pegloticase (8 mg every 2 weeks), a mammalian recombinant uricase conjugated to polyethylene glycol that is approved in the US for treatment of adult patients with chronic gout refractory to oral urate lowering therapy 2, the utility of these proposed criteria could be assessed. Objectives: To test the utility of the preliminary criteria to discern a complete response (CR) in subjects with chronic refractory gout treated with pegloticase (8 mg every 2 weeks). Methods: Data from two randomized clinical trials (RCT) evaluating the impact of pegloticase therapy in subjects with chronic refractory gout were examined. 2 Of this group of subjects, 42% had persistently lowered serum urate and 58% did not meet the urate-lowering endpoint of this RCT. Initially, individual patient data was reviewed to establish the frequency with which subjects, who were responders to pegloticase, met the proposed remission criteria. Mixed modeling was then employed on data from these subjects to determine the components of the model that best correlated with time of maximum benefit. Results: Of 34 pegloticase responders, 25 (73.5%) met the published criteria 1 of remission. However, pain assessment was often an outlier; data obtained by visual analogue scale and Medical Outcomes Study Short Form-36 questionnaire often differed. Mixed modeling was, therefore, carried out using the data obtained from the subjects meeting criteria for remission to determine the components that best correlated with time to maximum benefit. Other clinical outcome measures assessed in the clinical trial were also analyzed. Besides serum urate levels in the mixed modeling analysis, the components of response that best correlated with time of maximum benefit included assessment of tophi (analyzed photographically), number of swollen joints, number of tender joints and patient global assessment. Using these criteria, 25 of the responders (73.5%) and 29.4% of the entire pegloticase-treated population met criteria for a CR. The median time to reach a CR was 252 days (range: 126–966 days). Of interest, when a decrease in serum urate was omitted, 6 (12.2%) of the pegloticase nonresponders also met criteria for a CR. Patients receiving placebo did not achieve the composite outcome measure considered as CR. Conclusions: These results have defined criteria for achieving CR in individuals with chronic refractory gout treated with pegloticase and suggest that most individuals who persistently lowered their serum urate levels while on pegloticase reached criteria for CR in a median of 8.4 months. This composite CR definition can serve as an evidence-based target aiding the design and endpoints of future clinical trials. References: deLautour H, Taylor WJ, Adebajo A, et al. Arthritis Care Res. 2016;68:667–672. Sundy JS, Baraf HSB, Yood RA, et al. JAMA. 2011;306:711–720. Disclosure of Interest: N. Schlesinger Grant/research support from: AstraZeneca, Consultant for: Pfizer, AstraZeneca, Proteothera, Celgene, Horizon, P. Khanna Grant/research support from: AstraZeneca, Consultant for: Horizon, Ironwood, Selecta Bio, A. Yeo Consultant for: Horizon Pharma, P. Lipsky Consultant for: AstraZeneca, Celgene, EMD Serono, GSK, Horizon Pharma, Janssen, Medimmune, Pfizer, Roche, Sanofi, UCB